Transcriptome Profile Analysis of Strawberry Leaves Reveals Flowering Regulation under Blue Light Treatment - Yuntian Ye; Yongqiang Liu; Xiaolong Li; Qing Chen; Yong Zhang; Ya Luo; Zejing Liu; Yan Wang; Yuanxiu Lin; Yunting Zhang; Xiaorong Wang; Haoru Tang (International Journal of Genomics)
Blue light is an important signal that regulates the flowering of strawberry plants. To reveal the mechanism of early flowering under blue light treatment at the transcriptional regulation level, seedlings of cultivated strawberry (Fragaria × ananassa Duch.) “Benihoppe” were subjected to a white light treatment (WL) and blue light treatment (BL) until their flowering. To detect the expression patterns of genes in response to BL, a transcriptome analysis was performed based on RNA-Seq. The results identified a total of 6875 differentially expressed genes (DEGs) that responded to BL, consisting of 3138 (45.64%) downregulated ones and 3737 (54.36%) upregulated ones. These DEGs were significantly enriched into 98 GO terms and 71 KEGG pathways based on gene function annotation. Among the DEGs, the expression levels of genes that might participate in light signaling (PhyB, PIFs, and HY5) and circadian rhythm (FKF1, CCA1, LHY, and CO) in plants were altered under BL. The BBX transcription factors which responded to BL were also identified. The result showed that the FaBBX29, one of strawberry’s BBX family genes, may play an important role in flowering regulation. Our results provide a timely, comprehensive view and a reliable reference data resource for further study of flowering regulation under different light qualities.